2021
DOI: 10.21608/jpme.2021.68312.1078
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZrO2 Particles on the Tribological Properties of AlMg5 Alloy

Abstract: Aluminum based metal matrix composites are devoting more interest towards multiple applications due to their good thermal and mechanical properties. At this study, composites of AlMg5/ZrO2 with multiple gradients of ZrO2, were manufactured using stir casting technique. Microstructure, hardness and tribological properties of the composite were investigated. Pin-on-disk technique was used under wet conditions (3.5 wt. % NaCl solution) at different sliding speeds (varied from 0.125 to 0.5 ms -1 ) and applied load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This action can be due to decreasing the contact surface area of alloy where the added particles act as a load carrier and protect the surface from frictional forces. Also, the weight loss decreases due to the lubricating behavior of the emerging oxide layer [21].…”
Section: Hardness and Wear Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…This action can be due to decreasing the contact surface area of alloy where the added particles act as a load carrier and protect the surface from frictional forces. Also, the weight loss decreases due to the lubricating behavior of the emerging oxide layer [21].…”
Section: Hardness and Wear Behaviormentioning
confidence: 99%
“…It is a heavy mineral with excellent properties like; high hardness, high melting point, high chemical stability. This allows zircon to be utilized in important applications including; ceramics, refractory industries, foundry, abrasives, TV glass, electronics, pigments, and catalysts [1][2][3][4]. In Egypt, widespread placer deposits of black sand are intermittently distributed along the northern coast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was attributable to the improvement in reinforcement and matrix bonding with the reduction in particle size, and the worn surface corroborated the adhesive wear mechanism. Rashed et al [32] studied the effect of ZrO 2 particles on the tribological properties of an Al-Mg 5 composite fabricated using the stir casting technique. The results demonstrated that adding ZrO 2 up to 10% increased the hardness and wear resistance of the composite.…”
Section: Introductionmentioning
confidence: 99%